Magnet coils made from high-temperature superconductor - Jenkins, R; Jones, H; Burgoyne, J; Yang, M; Grovenor, C; Goringe, M (1996)
We review the progress we have made in constructing HTS coils and report our latest results. Also we describe the cryogen-free operation of one of our I-ITS coils cooled to 55 K using a Stirling cycle cryocooler. Lastly, we describe how 4 Oxford coils are being used in a project to investigate the controllability of HTS magnets in applications such as ''maglev'' suspension systems. We briefly report the initial findings of this work and describe developments in progress.